1994
DOI: 10.1136/oem.51.12.804
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma: attributable risk of asbestos exposure.

Abstract: Direct exposure to asbestos was determined from responses to three types of questions: specific queries as to any exposure to asbestos; occupational or non-vocational participation in any of nine specific activities thought to entail exposure to asbestos; and analysis of lifetime work histories. Indirect exposures were assessed through residential histories and reported contact with family members exposed to asbestos. Results-Among men with pleural mesothelioma the attributable risk (AR) for exposure to asbest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
184
2
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(200 citation statements)
references
References 49 publications
9
184
2
5
Order By: Relevance
“…Over the past 30 years, numerous epidemiology studies and industrial hygiene surveys have been conducted to characterize exposures to chrysotile and assess any respiratory health risks associated with vehicle repair. The epidemiology studies have shown that brake-repair activities are not associated with increases in the risk of developing asbestosis (Nicholson et al, 1984;Elliehausen et al, 1985;Marcus et al, 1987), lung cancer (Rushton et al, 1983;Lerchen et al, 1987;Benhamou et al, 1988;Vineis et al, 1988;Hansen, 1989;Gustavsson et al, 1990;Morabia et al, 1992;Wong, 1993Wong, , 2001Goodman et al, 2004), or mesothelioma (McDonald and McDonald, 1980;Petersen and Milham, 1980;Teta et al, 1983;Olsen and Jensen, 1987;Spirtas et al, 1985Spirtas et al, , 1994Woitowitz and Ro¨delsperger, 1994;Coggon et al, 1995;Teschke et al, 1997;Agudo et al, 2000;Milham and Ossiander, 2001; National Institute for Occupational Safety and Health (NIOSH), 2002;Hansen and Meersohn, 2003;Goodman et al, 2004;Hessel et al, 2004;Laden et al, 2004;McElvenny et al, 2005;Welch et al, 2005;Rolland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 30 years, numerous epidemiology studies and industrial hygiene surveys have been conducted to characterize exposures to chrysotile and assess any respiratory health risks associated with vehicle repair. The epidemiology studies have shown that brake-repair activities are not associated with increases in the risk of developing asbestosis (Nicholson et al, 1984;Elliehausen et al, 1985;Marcus et al, 1987), lung cancer (Rushton et al, 1983;Lerchen et al, 1987;Benhamou et al, 1988;Vineis et al, 1988;Hansen, 1989;Gustavsson et al, 1990;Morabia et al, 1992;Wong, 1993Wong, , 2001Goodman et al, 2004), or mesothelioma (McDonald and McDonald, 1980;Petersen and Milham, 1980;Teta et al, 1983;Olsen and Jensen, 1987;Spirtas et al, 1985Spirtas et al, , 1994Woitowitz and Ro¨delsperger, 1994;Coggon et al, 1995;Teschke et al, 1997;Agudo et al, 2000;Milham and Ossiander, 2001; National Institute for Occupational Safety and Health (NIOSH), 2002;Hansen and Meersohn, 2003;Goodman et al, 2004;Hessel et al, 2004;Laden et al, 2004;McElvenny et al, 2005;Welch et al, 2005;Rolland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the incidence of MPM has been increasing worldwide, 3 platinum-based chemotherapy is the only treatment that was scientifically verified to improve overall survival. 4 Immune checkpoint blocking antibodies, such as anti-cytotoxic T lymphocyte antigen-4 (CTLA-4) and anti-programmed death-1 (PD-1) antibodies, have shown a durable antitumor immune effect for several types of cancer, [5][6][7] and are under clinical investigation for MPM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, people who lived near those factories also suffered from the same fatal disease. (4) The characteristics of DMM are as follows: (i) it is associated with repeated asbestos exposure; (5,6) (ii) once diagnosed, prognosis is poor; (7) and (iii) it takes 30-40 years after the start of asbestos exposure for DMM to occur. (5,6) It is expected that the incidence of DMM in Japan will peak in 2025 with 100 000 predicted deaths from this neoplasm.…”
mentioning
confidence: 99%
“…(4) The characteristics of DMM are as follows: (i) it is associated with repeated asbestos exposure; (5,6) (ii) once diagnosed, prognosis is poor; (7) and (iii) it takes 30-40 years after the start of asbestos exposure for DMM to occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation